Anti-Tuberculosis Therapy: International, State, and Regional Pharmaceutical Care Policy - Egor Vadimovich Grebenev (Journal of Global Pharma Technology, 2016)
Today, pulmonary tuberculosis is a disease, which potentially threatens the whole humanity. Therefore, prompt actions should be taken. Tuberculosis is still the main threat to the global community. In this article, we investigated anti-tuberculosis therapy in an international, state and regional perspective. We have studied the use of combined therapy in treating tuberculosis patients. Thus, combining several anti-tuberculosis drugs in chemotherapy is deemed effective nowadays. We evaluated the drug supply for tuberculosis patients in regions and found out that patients have to take medicines constantly at all stages of anti-tuberculosis therapy. When analyzing the outcomes of cases of treatment of patients with tuberculosis and methods of increasing its effectiveness, we showed that insufficient adherence to treatment, as well as its insufficient control, provide almost half (44.6%) of unfavorable outcomes. Thus, it is necessary to develop methods and methods to motivate patients to comply with the recommendations of doctors. Keywords: Tuberculosis, Tuberculosis infection, Tuberculosis morbidity, TB services, Primary course of chemotherapy.